Effect of lubricant addition on bubble motion of refrigerant CO2 in the nucleate boiling process. (July 2022) - Huang, Yongfang; Xu, Xiaoxiao; Li, Xiaoxiao; Liu, Xinxin; Liu, Chao
Highlights: A lattice Boltzmann model is established to simulate bubble motion of CO2 /lubricant mixtures. The drag coefficient of a single bubble rising increases with increasing oil concentration. Lubricant oil weakens the heat transfer of nucleate boiling by bubble interactions. Abstract: In this study, the influence mechanism of lubricating oil on the heat transfer of CO2 flow boiling was investigated from a mesoscopic perspective. A multiphase and multicomponent lattice Boltzmann model was proposed to simulate the rising motion of CO2 bubbles in CO2 with a small amount of lubricating oil based on the pseudopotential model. There are few simulations of multicomponent with different chemical compositions in existing studies. Moreover, the original pseudopotential model exhibited increasing instabilities at higher viscosity ratios. The model proposed in this study realized the mesoscopic simulation of a CO2 /lubricant system by using an explicit forcing model to achieve numerical calculation under a high viscosity ratio and solve the evolution of the number density of each component to obtain the evolution of the macro parameters. The effectiveness of the model was verified using a Laplace's law simulation. Based on this model, the rising motions of single bubbles, double bubbles, and bubble groups under different oil concentrations were simulated. The effects of the lubricant on the rising velocity, morphology, and interaction of bubbles during bubble motion were analyzed in detail. The numerical results indicated that the variations in bubble shape decreased and drag force increased with the addition of oil. At an oil concentration of 0.05, the drag coefficient was 1.14 times higher than that under the oil-free condition. In addition, the presence of oil weakened the flow field disturbance caused by bubble interactions and resulted in the suppression for nucleate boiling.